How to Fully Benefit from Function Blocks of Foundation Fieldbus for Digital Cascade Control with High System Safety - Puthipong Yimvuthikul; Apinai Rerkratn; Thanit Trisuwannawat; Prasit Julsereewong; Amphawan Julsereewong (My University, 2015)
This paper presents a useful technique for configuring function blocks in Foundation Fieldbus H1 devices to form powerful digital cascade control that can take special action in the event of abnormal conditions. For high system safety, which often contradicts high availability, suggestions on how to fully benefit from standard function blocks with built-in interlock and bumpless transfer functionalities using parameter status are described. Experimental results obtained from a plant model for level-to-flow cascade control by configuring different status options, control options, and input/output options of the function blocks in response to undesired conditions are also included.
Keywords: Interlock; Real-Time Systems Scheduling